Efficacy and Safety of Traditional Chinese Medicine in Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-Analysis - Wang, Heping; Xu, Bowen; Zhang, Ying; Duan, Yuanyuan; Gao, Ruike; He, Haoqiang; Li, Xiuyang; Li, Jie (Frontiers in Pharmacology, 2021)
Introduction: There is still no clinically approved specific medicine to treat this disease. Prior systematic reviews (SRs) showed that traditional Chinese medicine (TCM) reduces the number of patients with severe disease and time to fever clearance, promotes clinical effectiveness, and improves chest images, and the negativity rate of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleic acid test. Few of the SRs arrived at a definitive conclusion, and more randomized controlled trials (RCTs) were published. We conducted this study to summarize the latest evidence of TCM in COVID-19. Methods: Databases were searched from December 2019 to July 2020, and updated to March 2021. Only RCTs evaluating the clinical efficacy and safety of TCM in the treatment of COVID-19 were included. Primary outcomes were clinical cure and the negativity of SARS-CoV-2 nucleic acid test. Secondary outcomes included clinical deterioration, ARDS, mechanical ventilation, death, time to fever clearance, duration of hospitalization, and chest imaging improvement. Safety outcomes included adverse events during treatment. Results: A total of 25 RCTs involving 2222 participants were selected in the systematic review, and 7 RCTs in the meta-analysis. The results showed that TCM plus routine treatment (RT) was significantly better than RT alone in clinical cure (risk ratio [RR] = 1.20, 95% confidence interval (CI) [1.04, 1.38]), and chest image improvement (RR = 1.22, [1.07, 1.39]), and could reduce clinical deterioration (RR = 0.39, [0.18, 0.86]), ARDS (RR = 0.28, [0.11, 0.69]), mechanical ventilation (RR = 0.30, [0.12, 0.77]), or death rate (RR = 0.28, [0.09, 0.84]). No significant difference between TCM and RT in the negativity of nucleic acid test (RR = 1.08, 95%CI [0.94, 1.23]) was observed. Conclusions: Synethized evidence of 21 outcomes in 7 RCTs showed moderate certainty that TCM plus RT may promote a clinical cure and chest image improvement compare to routine treatment alone, while reducing clinical deterioration, development of ARDS, use of mechanical ventilation, and death in patients with COVID-19. TCM treatment plus routine treatment may not promote the negativity of SARS-CoV-2 nucleic acid test than routine treatment alone. TCM treatment was found to be safe to patients with COVID-19.